2020
DOI: 10.3389/fnins.2020.577568
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Combined With a Machine Learning Algorithm Can Classify High-Risk First-Degree Relatives of Patients With Schizophrenia and Identify Correlates of Cognitive Impairments

Abstract: Schizophrenia (SCZ) is an inherited disease, with the familial risk being among the most important factors when evaluating an individual’s risk for SCZ. However, robust imaging biomarkers for the disease that can be used for diagnosis and determination of the prognosis are lacking. Here, we explore the potential of functional connectivity (FC) for use as a biomarker for the early detection of high-risk first-degree relatives (FDRs). Thirty-eight first-episode SCZ patients, 38 healthy controls (HCs), and 33 FDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…These procedures were processed in the “Prepare feature set” program. In the second step, Leave-one-out cross-validation (LOOCV) was used to evaluate the performance of the classifier ( Liu et al, 2020 ). In LOOCV, data from one subject was used as test data and the classifier is trained on the remaining dataset.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These procedures were processed in the “Prepare feature set” program. In the second step, Leave-one-out cross-validation (LOOCV) was used to evaluate the performance of the classifier ( Liu et al, 2020 ). In LOOCV, data from one subject was used as test data and the classifier is trained on the remaining dataset.…”
Section: Methodsmentioning
confidence: 99%
“…The translational applicability of such data to clinical practice should be based on inferences at the individual rather than group level. With recent advancements in the field of machine learning, such as the support vector machine (SVM) model, a multivariate pattern recognition machine learning (ML) technique especially well-suited for discriminating high-dimensional rsFC fMRI data, measurements derived from fMRI combined with artificial intelligence algorithms have led to improvements in diagnoses, classification, and treatment outcome prediction for a range of situations ( Zhao et al, 2018 ; Liu et al, 2020 ). Furthermore, multivariate machine learning techniques are more sensitive to differences that are subtle and spatially distributed because they consider inter-regional correlations, which might be undetectable using group comparisons ( Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike traditional group-level univariate analysis, cutting-edge machine learning techniques can detect differences that are subtle and spatially distributed and have been indicated to improve diagnoses, classification, and treatment-outcome prediction in a range of situations. 13 , 14 However, to our best knowledge, studies using DTI and machine learning strategies for SD vulnerability prediction are rare. In the current study, we applied a linear support vector machine learning approach to investigate whether the WM diffusion metrics can predict vulnerability to SD.…”
Section: Introductionmentioning
confidence: 99%
“…With the recent advancements in the field of machine learning, measurements derived from rs-fMRI combined with artificial intelligence algorithms have led to the improvements in the diagnosis, classification, and treatment outcome prediction for a range of diseases, in particular, for schizophrenia [ 10 ]. Our pervious study has indicated that functional connectivity can be a sensitive marker to differentiate SCZ from healthy controls (HCs) [ 11 ]; baseline spontaneous regional activities were also found to be predictive of early response to treatment for SCZ [ 12 ]. Because SCZ is associated with widespread changes in functional networks, graph-based measurements of network organization, such as degree centrality, might have potential in predicting treatment effects.…”
Section: Introductionmentioning
confidence: 99%